Effects of the in vivo treatment of radioactive implant-induced skin wounds with adipose-derived mesenchymal stem cells (ASCs) - Katarzyna Siennicka; Anna Słysz; Paweł Piotrowski; Ewelina Gruszczyńska; Anna Kulik; Zygmunt Pojda (Nowotwory)
INTRODUCTION: Adipose tissue-derived mesenchymal stem cells (ASCs) play a crucial role in healing skin wounds causedby radiation. Herein is demonstrated a patented, novel radioactive implant designed for research on the effectsof radiation and the wound repair process. MATERIAL AND METHODS: Inbred LEW/W rats were used as both ASCs donors and recipients of radiation. A radiationwound was induced by inserting a I125 implant under the dorsal skin. After irradiating the skin with doses of 10 Gyover 3 days or 18 Gy over 5.5 days, ASCs were injected into the wound area at weekly intervals. RESULTS: Treatment with ASCs altered the immune system’s response to the radiation wound, promoted neoangiogenesisand reduced necrotic areas at the wound site. CONCLUSIONS: The present in vivo irradiation technique may enhance the understanding and refinement of brachytherapytechniques, utilizing tissue-implanted radiation sources with the ability to shield adjacent tissues effectively.